Quasi-Transitivity, Rational Choice and Collective Decisions - Sen, A. (Review of Economic Studies, 1969)
Journal Article Quasi-Transitivity, Rational Choice and Collective Decisions Get access Amartya Sen Amartya Sen Harvard University and Delhi School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 3, July 1969, Pages 381–393, https://doi.org/10.2307/2296434 Published: 01 July 1969 Article history Received: 15 September 1968 Received: 10 February 1969 Published: 01 July 1969